THE ANTECEDENT OF REGIONAL FINANCIAL REPORT QUALITY - Slamet Widodo; Akram Harmoni Wiardi; Tri Deni Prabowo (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2019)
The objective of this research is to analyze the competency, the comprehension of the government accounting standard, the implementation of internal control system and the quality of financial report in Kepahiang Regency.This Research was done to financial managers. The data were gathered by distributing the questionnaire to 102 respondents. This study used the data analysis of Multiple Linear Regression. The result of this research showed that competency has significant effect on the quality of financial report. The comprehension of the government accounting standard has significant effecton the quality of financial report. The implementation of internal control system significant effect on the quality of financial report